E-Module Development on 3D Pageflip Professional Based Straight Motion Material - Farni, Evi Ramna; Rahi, Annisa (Program Magister Teknologi Pendidikan Universitas Jambi, 2016)
The research aims to produce a Discovery Learning-based electronic module on rectilinear motion material for class X SMA that is valid and feasible and to determine students' perceptions of the module developed. The model used is the ADDIE development model (analyze, design, develop, implement and evaluate). The test subjects were class X MIA 4 SMA Negeri 10 Jambi City. The instruments used were student needs analysis questionnaires, observation documents, expert validation questionnaires and student perception questionnaires. Data analysis techniques in the form of validation questionnaire scores and student perception questionnaires were carried out using descriptive statistics. Meanwhile, analysis of data from observations and validator suggestions was carried out in a qualitative descriptive manner. The results showed that students' perceptions of the module cover design were 13.89 (very good), the module content was 21.69 (very good), the module software was 12.91 (good), the module presentation was 3.23 (good), and the language component was 13. .37 (excellent). From these four aspects it can be concluded that the Electronic Module Based on Discovery Learning in Straight Motion for class X SMA is suitable for use in the good category.